DINAMIKA POLITIK SEPULUH TAHUN PERDAMAIAN DI ACEH (Analisis Politik Kawasan Pesisir Timur Aceh) - Usman Usman (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
The aim of this study is to find out the situation, condition, and politic impact towards Acehnese society in ten years after reconciliation. The qualitative research is used in this study which the result to create a systemic, factual, and accurate description of the facts, characteristics as well as the related phenomena which is being investigation. The collecting data, the researcher used interview and field observation in Lhoksemawe, North Aceh, and Bireun. The result found that the political dominance in the East Coast Aceh is still controlled by Gerakan Aceh Merdeka which is affecting the political policies between Central Government and Aceh Government. For instance, it emerge the major conflicts within Gerakan Aceh Merdeka, such as Din Minimi, and political party rivalry. This political dynamics phenomena also affects the East Coast society life, such as political violence, intimidation, terror, and other political violences